Prevalence of Spinal Injuries among Autopsied Cases of Traumatic Deaths - Acharya, Apurba; Bhattarai, Kushal; Rokaya, Poojan Kumar; Aryal, Umesh Raj; Kaphle, Sushma; Bista, Binamra; Khatiwada, Amit (Journal of Nepal Health Research Council, 2025)
Background: Traumatic deaths, resulting from spinal injuries are significant issue in Nepal. The study aims to assess the prevalence of spinal injuries amongst the traumatic death cases brought in for autopsy in Jumla and to provide their socio-demographic profile.Methods: This is a descriptive cross-sectional study done in Karnali Academy of Health Sciences (KAHS) from 16th July 2021 to 16th July 2023 incorporating all the traumatic deaths brought for autopsy. The data was collected using a proforma which included the modality of trauma, spinal involvement, seasons associated with trauma and demographic variables of the deceased. The data was analyzed using both Microsoft excel and SPSS 23.0. Results: A total of 55 cases were brought for autopsy following traumatic death with road traffic accident (45.45%) and fall injuries (29.1%) being the most common mode of trauma. Among all traumatic deaths, 29.1% cases presented with spinal injuries. The cervical spine (68.8%) was the most commonly affected spine followed by thoracic (12%), lumbar spine (6.3%) and two cases with multiple spinal involvement. Of all the spinal injury cases in traumatic deaths, the highest and the lowest number of cases occurred during spring and summer season respectively.Conclusions: Traumatic deaths caused by spinal injuries after fall and road traffic accidents is a common phenomenon in Jumla. Thus, timely preventive measures associated with these deaths needs to be addressed to reduce them. Keywords: Autopsy; deaths; Jumla; spinal injuries; trauma.